THE ESSENCE OF THE GLOBAL WEALTH PYRAMID* - Ivan LUCHIAN; Iulita BIRCA; Mihaela BIRCA (Economica, 2020)
The net wealth is an economic category composed of all real and financial assets, from which value all balances of existing debts of a natural person are deducted. Global statistical technologies allow highlighting the total number of adults and their net wealth. By summing personal net wealth, global wealth is obtained, which finds its reflection in the pyramid of global wealth. The aim of the study was to identify the essence and determine the dynamics of the global wealth pyramid in total and structural aspect and its distribution by wealth and geographical levels. The study allowed to detect a huge extrapolation between people’s categories with a different level of wealth, an important discrepancy has been established in the distribution of global wealth in regions and between countries, which will contribute to distortions of different genres: economic, financial, demographic, social, ecological, which can be the cause of different global cataclysms with unpredictable consequences.